(untitled) (INNOVATIVE ECONOMY, 2021)
Tripak M.M. PARADIGM OF ECONOMIC AND MATHEMATICAL MODEL OF RATING OF EDUCATIONAL INSTITUTIONS Purpose. The aim of the article is the development of a mathematical model that can be used to determine the ranking of the best educational institutions in the region and systematize educational institutions into appropriate clusters, taking into account their industry significance, ownership, efficiency of public funding and own revenues that effectively use innovation and research potential. Methods of research. The methodological and theoretical basis of the study was the theories and views presented in the works of scientists. The results of the study were obtained using both general and special methods of scientific knowledge. The general theoretical context of the research is considered on the basis of the dialectical method; the method of analysis and synthesis was used in identifying global problems of institutions in world-class higher education. Argumentation of theoretical provisions that characterize the patterns of functioning of research, production and educational institutions in the global space, formed on the system analysis, the laws of logic, the method of scientific abstraction. Mathematical tools were used to determine the amount of fixed assets, total expenditures and revenues of general and special funds of the budgetary institution. Findings. An economic and mathematical model and a simplified formulation of the optimization problem have been developed. Mathematical modelling was performed, which made it possible to construct a model as a system of mathematical relations describing certain technological, economic or other processes. Originality. The article singles out and substantiates the model that allows, unlike existing ones, to form clusters of educational institutions with the help of economic and mathematical modelling, taking into account their sectoral significance, form of ownership, efficiency of public funding and own revenues that effectively use innovation and research potential. Practical value. The results of clustering based on a substantiated model of educational institutions will allow to obtain additional funding for higher education institutions. Key words: budgetary institutions, institutions, mathematical model, rating, general and special funds, budgetary allocations, fixed assets.